Pengaruh Pemberian Ekstrak Etanol 70 % Daun Jambu Air (Syzygium samarangense) Kultivar Merah Muda (Masam Manis Pink) Terhadap Penurunan Kadar Gula Darah Tikus Putih (Rattus norvegicus) Yang Diinduksi Aloksan - Latifani, Nadia Fatkhy; , Riandini Aisyah, S.Si, M.Sc; , Dr. dr. EM Sutrisna, M.Kes (2016)
Background : Syzygium samarangense leaf contains flavonoid, tannins, and chalcone phytochemicals which have antidiabetic effect by increasing insulin sensitivity, improving pancreatic β cell proliferation, working as a potent inhibitor of α-glucosidase enzyme, as well as being a potent antioxidant to a pancreatic damage due to free radicals. Objective : To determine the effect 70% ethanolic extract of pink cultivars (masam manis pink) wax apple (Syzygium samarangens) leaf in reducing blood glucose levels in alloxan-induced diabetic Rattus norvegicus. Methods : This study is an experimental labolatory with Pre and Post Test with Control Group Design. The subject of study was Syzygium samarangense leaf and the test animal were 30 male rats (Rattus norvegicus) devided into 6 groups consisted of 5 rats each. Each group underwent initial check of blood glucose (GD 1) on the day 0 and after that they were injected with 30 mg/200g alloxan, then underwent blood glucose pretest (GD 2) check on day 4. Negative control group was given treatment with aquadest, positive control group was treated glibenclamide 126 mg/200g bw, Group III, IV, V, and VI were orally given 210 mg/Kg bw, 245 mg/Kg bw, and 280 mg/Kg bw ethanolic ectract of Syzygium samarangense leaf respectively. All group were treated for 7 days then were examined as a post-test blood glucose (GD 3) on day 11. The obtained data were analyzed by one-way ANOVA test and LSD (Least Significant Difference) test. Result : ANOVA test result obtained p value = 0,000 (p < 0,05 ) it means that on all six groups there are at least one group that is significantly different. LSD test obtained (-) control - (+) control = 0,000, (-) control - dose I = 0,000, (-) control - dose II = 0,000, (-) control - dose III = 0,000, (-) control - dose IV = 0,000, (+) control - dose I = 0,000, (+) control - dose II = 0,000, (+) control - dose III = 0,003, (+) control - dose IV = 0,141, dose I - dose II = 0,239, doseI - dose III = 0,006, dose I - dose IV = 0,000, dose II - dose III = 0,089, dose II - dose IV = 0,001 and dose III - dose IV = 0,083, p <0.05 indicates that there are significant differences between groups. Conclusion : The 70% ethanolic extract of pink cultivars (masam manis pink) wax apple (Syzygium samarangens) leaf with the dose of 175 mg/Kg bw, 210 mg/Kg bw, 245 mg/Kg bw, and 280 mg/Kg bw were able to reduce blood glucose levels in alloxan-induced diabetic Rattus norvegicus with reduction percentage was 36,32 %, 41,95 %, 49,14 and 55,74 %, respectively.